Post-traumatic epilepsy: current and emerging treatment options - Szaflarski, Jerzy P (Dove Medical Press, 2014)
Traumatic brain injury (TBI) leads to many undesired problems and complications, including immediate and long-term seizures/epilepsy, changes in mood, behavioral, and personality problems, cognitive and motor deficits, movement disorders, and sleep problems. Clinicians involved in the treatment of patients with acute TBI need to be aware of a number of issues, including the incidence and prevalence of early seizures and post-traumatic epilepsy (PTE), comorbidities associated with seizures and anticonvulsant therapies, and factors that can contribute to their emergence. While strong scientific evidence for early seizure prevention in TBI is available for phenytoin (PHT), other antiepileptic medications, eg, levetiracetam (LEV), are also being utilized in clinical settings. The use of PHT has its drawbacks, including cognitive side effects and effects on function recovery. Rates of recovery after TBI are expected to plateau after a certain period of time. Nevertheless, some patients continue to improve while others deteriorate without any clear contributing factors. Thus, one must ask, ‘Are there any actions that can be taken to decrease the chance of post-traumatic seizures and epilepsy while minimizing potential short- and long-term effects of anticonvulsants?’ While the answer is ‘probably,’ more evidence is needed to replace PHT with LEV on a permanent basis. Some have proposed studies to address this issue, while others look toward different options, including other anticonvulsants (eg, perampanel or other AMPA antagonists), or less established treatments (eg, ketamine). In this review, we focus on a comparison of the use of PHT versus LEV in the acute TBI setting and summarize the clinical aspects of seizure prevention in humans with appropriate, but general, references to the animal literature.